2018
DOI: 10.33549/physiolres.933776
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Protects Against Stress-Induced Anxiety- and Depression-Like Behavior and Improves Memory in Male Mice

Abstract: The present study evaluates the protective role of Quercetin (Quer), against immobilization stress- induced anxiety, depression and cognition alteration in mice using behavioral and biochemical parameters. 24 adult Albino mice were distributed into 2 groups vehicle (n=12; 1 ml/kg) and Quer injected (n=12; 20 mg/kg/ml). The animals received their respective treatment for 14 days. On day 15, after the drug administration, animals were sub-divided into 4 groups (n=6); (i) unstressed + vehicle; (ii) stressed + veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 62 publications
8
63
0
1
Order By: Relevance
“…Similar with the results of fluoxetine, administration of quercetin could also improve the bodyweight gain, increase the SPI in the SPT, and decrease the immobility time in the FST, although it had no effect on the performance in the OFT. Together with the findings that quercetin could reduce the immobility time of mice in the FST and tail suspend test in our preliminary study (attached in the Supplementary Materials) and relieve the depression-like behavior of stressed mice (Samad et al, 2018), our results suggested again the antidepressant effect of quercetin. Moreover, our results showed a task-related improvement effect of quercetin on the learning and memory.…”
Section: Fang Et Alsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar with the results of fluoxetine, administration of quercetin could also improve the bodyweight gain, increase the SPI in the SPT, and decrease the immobility time in the FST, although it had no effect on the performance in the OFT. Together with the findings that quercetin could reduce the immobility time of mice in the FST and tail suspend test in our preliminary study (attached in the Supplementary Materials) and relieve the depression-like behavior of stressed mice (Samad et al, 2018), our results suggested again the antidepressant effect of quercetin. Moreover, our results showed a task-related improvement effect of quercetin on the learning and memory.…”
Section: Fang Et Alsupporting
confidence: 84%
“…Our previous results demonstrated that it could bind to beta amyloid (Ab)1-40 and Ab1-42 in monomer or fibril state. Recently, it has been reported that quercetin could protect against stress-induced anxiety-and depression-like behavior and improve memory in male mice (Samad et al, 2018). Consistently, results of our preliminary study showed that it could shorten the immobility time of mice in the forced swimming test (FST) and tail suspending test, though the mechanism remains unclear.…”
Section: Introductionsupporting
confidence: 83%
“…It is widely accepted that exposure to the chronic stress causes the overproduction of free radicals and the suppression of endogenous antioxidant enzymes, which are associated with the cognitive dysfunction [24,25]. In agreement with previous reports [26,27], our present data showed that the amounts of MDA, a biomarker of lipid peroxidation, were significantly increased in the frontal cortex and hippocampus of the UCMS mice.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in line with those suggesting that GABA antagonism can be anxiolytic. For example, quercetin, a negative allosteric modulator for GABAA receptors (GABAARs), reduces GABAergic transmission in the PFC (Fan et al, 2018) and has stress-protective and anxiolytic effects (Bhutada et al, 2010;Mehta et al, 2017;Samad et al, 2018). Another negative allosteric modulator for α5-containing GABAARs, MRK-016, also exhibits antidepressant actions (Zanos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%